Early Education and Gender Differences - Daniela Del Boca; Enrica Maria Martino; Elena Claudia Meroni; Daniela Piazzalunga (Institute of Labor Economics (IZA), 2019)
A rich strand of the economic literature has been studying the impact of different forms of early childcare on children cognitive and non-cognitive development in the short and medium run, and on a number of educational, labor market, and life outcomes in the long run. These studies agree in assessing the importance of the first years of life on future outcomes, and identify early childhood interventions as a powerful policy instrument to boost child development. Furthermore, most research agrees in identifying stronger beneficial effects among children from disadvantaged backgrounds, making a case for the role of childcare policies in reducing inequality. Instead, heterogeneity of results across gender is less clear-cut. Yet, it is important to understand how childcare arrangements differently affect boys and girls, to figure out how to boost cognitive and non-cognitive development of young children and how to reduce gender gaps later in life. Our paper offers a comprehensive review of the literature on early childcare impacts, shedding light on the heterogeneous effects across genders, considering the role of institutional background, type of the intervention, and age of the child. We also present some empirical results on the Italian case which indicates that gender differences in the outcomes is lower among children who attended an impact toddler center, while it is higher and more often statistically significant for those who received informal care. This result confirms the positive and equalizing role of early public childcare.
Keywords: J13; J16; 330; childcare; child development; cognitive skills; non-cognitive skills; gender differences